2012
DOI: 10.1007/s10295-011-1007-7
|View full text |Cite
|
Sign up to set email alerts
|

Poly(β-L-malic acid) production by diverse phylogenetic clades of Aureobasidium pullulans

Abstract: Poly(β-L-malic acid) (PMA) is a natural biopolyester that has pharmaceutical applications and other potential uses. In this study, we examined PMA production by 56 strains of the fungus Aureobasidium pullulans representing genetically diverse phylogenetic clades. Thirty-six strains were isolated from various locations in Iceland and Thailand. All strains from Iceland belonged to a newly recognized clade 13, while strains from Thailand were distributed among 8 other clades, including a novel clade 14. Thirty of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 25 publications
0
51
0
1
Order By: Relevance
“…Most of these strains produced pullulan with only a few exceptions, such as the strains NRRL 58539 and NRRL 58543. However, the structure of EPS produced from the NRRL 58539 and NRRL 58543 strains have not been characterized in previous reports 5,7 . This study is the first report of aubasidan-like β-glucan-producing strains of A. pullulans isolated in Thailand.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most of these strains produced pullulan with only a few exceptions, such as the strains NRRL 58539 and NRRL 58543. However, the structure of EPS produced from the NRRL 58539 and NRRL 58543 strains have not been characterized in previous reports 5,7 . This study is the first report of aubasidan-like β-glucan-producing strains of A. pullulans isolated in Thailand.…”
Section: Discussionmentioning
confidence: 98%
“…Previous multilocus DNA sequence analyses suggested that both strains were not A. pullulans var. pullulans because they grouped in a different clade 5,7 . However, representative strains of the three varieties of A. pullulans, (var.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMLA can be produced by either chemical synthesis [10] or microbial fermentation [17]; the latter approach has been extensively investigated. Leathers et al [17] did signiWcant work on PMLA production by strains of Aureobasidium pullulans representing genetically diverse phylogenetic clades, some of which included strains produced relatively high levels of PMLA.…”
Section: Introductionmentioning
confidence: 99%
“…Some isolates of A. pullulans produce semiochemicals (Davis et al, 2012) that influence wasp behaviour in nature and that may be involved in dispersal of members of the genus Aureobasidium, while other isolates produce large amounts of the extracellular polysaccharide (EPS) pullulan (Manitchotpisit et al, 2009), a polysaccharide with many valuable industrial and medical uses (Leathers, 2002;Cheng et al, 2011). Still other isolates biosynthesize products that have commercial value such as laccase (Rich et al, 2011), xylanase (Manitchotpisit et al, 2009) or poly b-L-malic acid (Manitchotpisit et al, 2012).…”
mentioning
confidence: 99%